Standardization of 64Cu activity. (September 2018) - Bergeron, D.E.; Cessna, J.T.; Fitzgerald, R.; Pibida, L.; Zimmerman, B.E.
Abstract: The complex decay scheme that makes 64 Cu promising as both an imaging and therapeutic agent in medicine also makes the absolute measurement of its activity challenging. The National Institute of Standards and Technology (NIST) has completed a primary activity standardization of a 64 CuCl2 solution using the 4πβ(LS)-γ(NaI) live-timed anticoincidence (LTAC) counting method with a combined standard uncertainty of 0.51 %. Two liquid scintillation (LS) counting methods were employed for confirmatory measurements. Secondary measurements were made by high-purity germanium detectors, pressurized ionization chambers (IC), and a well-type NaI(Tl) counter. Agreement between the LTAC-based standard and standards from other laboratories was established via IC calibration factors. Poor agreement between methods and with theoretical IC responses may indicate a need for improved β +/- branching probabilities and a better treatment of β +/- spectra. Highlights: The activity of a 64 Cu solution was measured by live-timed anticoincidence (LTAC) counting. Liquid scintillation counting with efficiency tracing or triple-to-double coincidence ratio provided confirmatory measurements. Between-method discrepancies may indicate a need for revisiting recommended nuclear data.